Carrier detection in families affected by Duchenne muscular dystrophy using Multiplex Ligation - Dependent Probe Amplification = Ứng dụng kỹ thuật Multiplex Ligation - Dependent Probe Amplification xác định người lành mang gen bệnh trong các gia đình bị ả - Nguyễn, Thị Tường An (ĐHQGHN, 2017)
56 p. + CD-ROM